Pertussis seroepidemiology in women and their infants in Sarlahi District, Nepal. Issue 48 (4th December 2017) - Hughes, Michelle M.; Englund, Janet A.; Edwards, Kathryn; Yoder, Sandra; Tielsch, James M.; Steinhoff, Mark; Khatry, Subarna K.; LeClerq, Steven C.; Katz, Joanne
Abstract: Background: Infants are at greatest risk for pertussis morbidity and mortality. Maternal vaccination during pregnancy has been shown to prevent pertussis in young infants in high- and middle-income countries. However, data on the levels of maternal pertussis antibodies and the efficiency of transplacental transfer in low-income South Asian settings are limited. Objective: To estimate the prevalence of maternal pertussis antibodies and the efficiency of transplacental transfer in rural southern Nepal. Design/methods: Paired maternal-infant blood samples were collected from a subsample of participants in a randomized, controlled trial of maternal influenza immunization (n = 291 pairs). Sera were tested by enzyme-linked immunosorbent assays for pertussis toxin, filamentous hemagglutinin, pertactin, and fimbriae. Maternal and infant pertussis antibody levels and transplacental transfer efficiency were determined and potential factors associated with both were assessed. Results: Elevated maternal antibodies to pertussis toxin, suggesting recent pertussis infection, were rarely detected (4%, tested n = 305). However, paired maternal-cord sera were highly correlated across all antibodies; transplacental antibody transfer ratios for pertussis toxin were 1.14 (n = 291, 95% CI 1.07–1.20); filamentous hemagglutinin 1.10 (n = 120, 95% CI: 1.01–1.20); fimbriae 2/3 1.05 (n = 120, 95% CI: 0.96–1.15) and pertactin 0.96 (n = 289, 95% CI: 0.91–1.00). Older gestational age was associated with increased pertussis toxin and decreased fimbriae 2/3 antibody transport. Conclusions: A low prevalence of maternal antibody to all four pertussis antigens was noted in Nepal, but transplacental antibody transfer was efficient. No consistent demographic factors were associated with elevated maternal antibody levels or efficiency of transplacental transfer. If an increase in infant pertussis disease burden was detected in this population, maternal immunization could be an effective intervention to prevent disease in early infancy.